Addressing the challenges of implementation of high-order finite volume schemes for atmospheric dynamics of unstructured meshes - Tsoutsanis, Panagiotis; Drikakis, Dimitris (European Congress on Computational Methods in Applied Sciences and Engineering, 2016)
The solution of the non-hydrostatic compressible Euler equations using Weighted Essentially Non-Oscillatory (WENO) schemes in two and three-dimensional unstructured meshes, is presented. Their key characteristics are their simplicity; accuracy; robustness; non-oscillatory properties; versatility in handling any type of grid topology; computational and parallel efficiency. Their defining characteristic is a non-linear combination of a series of high-order reconstruction polynomials arising from a series of reconstruction stencils. In the present study an explicit TVD Runge-Kutta 3rd -order method is employed due to its lower computational resources requirement compared to implicit type time advancement methods. The WENO schemes (up to 5th -order) are applied to the two dimensional and three dimensional test cases: a 2D rising.
Keywords: WENO; Unstructured meshes; Non-hydrostatic; Rising bubble